Accumulation of Heavy Metals in Lettuce (Lactuca sativa L.) cultivated in the gardening site of Houéyiho in Cotonou (Bénin) - CHIDIKOFAN, Floriane; ADJAKPA, Boco Jacques; AHOTON, ESSÈHOU LÉONARD; AKPO, Léonard Elie; WETHE, J. (My University, 2012)
The market gardening production in an urban environment is an activity which contributes to the improvement of population livelihood. Therefore, a study on Lactua sativa L. was undertaken at Houéyiho in order to determine the concentration of heavy metals in this legume.The methodology adopted is based on site observation, agronomic trial and laboratory analysis of heavy metals concentration (lead, cadmium, copper and zinc) in soil, water and lettuce sampled from Houéyiho market gardening site. The results of this work showed that: i) the soil of the experimental site was polluted by heavy metals including zinc (103.88 mg/kg dry material), lead (19.14 mg/kg dry material) and copper (3.12 mg/kg dry material); ii) all lettuce leaves contained residues of heavy metals beyond the standards of Codex Alimentarius. The rate of lead (metal very dangerous to human health) is nine times as big than the limit (0.3 mg/kg dry material) in leaves of lettuce with fertilizer; 7.6 times as big in leaves witness and 6 times in those with compost. These heavy metals are absorbed by the plants of lettuce through the atmospheric air and soil.
Keywords: Heavy metals; lettuce; compost; Houéyiho; Bénin